Improving Students’ Grammar Mastery of Noun Clauses By Using Teacher’s Correction Technique - Safra Apriani Zahraa; Halim Dwi Putra; Fanalisa Elfa; Ari Satria (ELT-Lectura, 2023)
This study aims to know the improvement of students’ grammar mastery by using Teacher Correction technique. The research method used was a Classroom Action Research (CAR). The research data included the results of the pretest and posttest regarding noun clauses. The data collection techniques used were classroom observation, interviews, pretest and posttest. The results of this study showed that the average score of students was 24.6 in pretest, increased from to in Cycle I to 39.2 in 69.2 II. It indicated that the use of Teacher Correction technique could improve students' understanding in mastering noun clauses. This technique can be one of effective ways for teachers or lecturers to teach noun clauses.